HUBUNGAN ANTARA BIMBINGAN PRIBADI DENGAN ASERTIVITAS SISWA KELAS VIII MTS NEGERI YOGYAKARTA 1 - Nur Aeni Sanjaya; Nailul Falah (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2018)
This study aims to determine the relationship between personal guidance and assertiveness students of class VIII MTs Negeri Yogyakarta 1 using a quantitative approach. In this study there is one independent variable and one dependent variable. The independent variable in this research is personal guidance (X), while the dependent variable is assertiveness (Y). This study is research population with total population of 58 students. The main data collection techniques such as scale, while interviewing and documentation as a complementary data. Data analysis using Product Moment correlation study from Pearson for obtained the results of hypothesis testing, with the help of SPSS 16.0 for Windows. The results of this study indicate that there is a positive and highly significant relationship between personal guidance and assertiveness students of class VIII MTs Negeri Yogyakarta 1 which has a correlation coefficient of 0.618 with sig. (2.tailed) = 0,000 with N = 58 at 1% significance level. From these data it can be concluded that there is a positive relationship and very significant, then the hypothesis is accepted and proved true. That is, the higher the personal guidance the higher the student's assertiveness, on the contrary if it gets lower personal guidance, the lower the student's assertiveness.  Keywords: Personal Guidance, Assertiveness